2020
DOI: 10.1177/0743558419897386
|View full text |Cite
|
Sign up to set email alerts
|

Black Students’ Perceptions of School Ethnic-Racial Socialization Practices in a Predominantly Black School

Abstract: Ethnic-racial socialization describes messages and practices that teach youth about their racial and/or ethnic group membership and the role of race in society. Despite a wealth of research on families, little work has considered school socialization practices. The current article uses a framework of school racial socialization to explore six socialization messages reported in a predominantly Black public charter school in an urban area. In focus group and individual interviews, 21 African American students (7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 55 publications
(65 reference statements)
3
33
0
Order By: Relevance
“…Although 70 of the racial knowledge statements had no clear supporting evidence, most of the remaining statements were linked to one (or more) of the following sources of information: specific racial stories the child experienced (95 statements); socialization messages received from family members (47 statements); school curricula and other educational resources, like museums (54 statements); racialized patterns that they saw in the media (e.g., in the news, in books, in movies; 102 statements); or patterns that they observed or perceived in the world around them (e.g., racial segregation in classrooms and lunchrooms or different housing conditions of different racial groups in the city; 158 statements). Thus, as in other studies (e.g., Byrd & Hope, 2020; Umaña‐Taylor & Hill, 2020), participants in our sample reported learning about their group's racial history through direct messages from parents as well as in history books, museums, and other cultural sites. On the other hand, we found that youths’ racial knowledge statements about the modern social significance of race were often linked to the racialized experiences and observable racial disparities that they repeatedly encountered within or across settings (especially in school and in the news).…”
Section: Resultssupporting
confidence: 74%
“…Although 70 of the racial knowledge statements had no clear supporting evidence, most of the remaining statements were linked to one (or more) of the following sources of information: specific racial stories the child experienced (95 statements); socialization messages received from family members (47 statements); school curricula and other educational resources, like museums (54 statements); racialized patterns that they saw in the media (e.g., in the news, in books, in movies; 102 statements); or patterns that they observed or perceived in the world around them (e.g., racial segregation in classrooms and lunchrooms or different housing conditions of different racial groups in the city; 158 statements). Thus, as in other studies (e.g., Byrd & Hope, 2020; Umaña‐Taylor & Hill, 2020), participants in our sample reported learning about their group's racial history through direct messages from parents as well as in history books, museums, and other cultural sites. On the other hand, we found that youths’ racial knowledge statements about the modern social significance of race were often linked to the racialized experiences and observable racial disparities that they repeatedly encountered within or across settings (especially in school and in the news).…”
Section: Resultssupporting
confidence: 74%
“…First, teachers and staff can explicitly communicate beliefs and values about race through their speech and curriculum choices (e.g., Aronson & Laughter, 2016; Walton et al., 2014). They can also implicitly socialize, for example, by avoiding conversations about race or by only focusing on racism as a historical artifact (e.g., Byrd & Hope, 2020). In fact, research suggests that most schools take a color‐evasive approach (e.g., avoiding racial topics and discussions) (Hazelbaker & Mistry, in press; Schofield, 2006; Walton, et al., 2014).…”
Section: The School Ers Transmission Modelmentioning
confidence: 99%
“…Schools might also emphasize US centric holidays like President's Day over other types of celebrations. Although mainstream values are often observable in schools (e.g., Perry, 2001), it is not clear to what extent adolescents are explicitly aware of mainstream socialization messages; instead, youth may perceive the messages as not related to race or culture (Byrd & Hope, 2020).…”
Section: The School Ers Transmission Modelmentioning
confidence: 99%
“…We did not find studies that reported outcomes across all of these domains and doing so would be a significant undertaking, but perhaps a necessary one, to understand how these outcomes work together. Educators could collaborate with psychologists who have developed assessments of critical consciousness and cultural affiliation (Byrd & Hope, 2020; Diemer et al, 2017). New instruments may be needed for young children or school contexts.…”
Section: Discussionmentioning
confidence: 99%